Tathbīq Tharīqah al-Tamyīz fī Ta’līm Qawāid al-Lughah al-‘Arabiyah li Tarqiyah Mahāah Qirāah Kutub al-Turās - Azizurahman, Azizurahman; Fadli, Adi; Suryani, Erma (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Purpose- This paper describes the implementation and evaluation system of the Tamyiz method in learning Arabic grammar to improve the skill of reading heritage books in the Dinul Qoyyim Islamic Boarding School, Gunung Sari West Lombok, Halaqah Mubtadi. Design/ Methodology/Qualitative - This field research uses a qualitative descriptive analysis approach, where the data sources consist of primary and secondary data sources, using observation, interview and documentation techniques. At the same time, data analysis is done by data reduction, presentation and verification. Test the validity of the data using validity testing in the form of extended observations, triangulation, increasing accuracy, negative case analysis, and organ screening. Findings- The research findings indicate that the Tamyiz method, implemented through repetitive and varied exercises such as reading, memorization, and singing, significantly enhances students' understanding of grammar and morphology. Using the book "Fathul Qarib" as the primary text facilitates students' comprehension of Arabic grammar. The rhythm of singing exercises, inspired by children's songs and popular prayers, makes students more active in learning. Improvements in understanding and memorizing sentences, as well as ease in reading classical texts (kutubut turath), demonstrate the effectiveness of the Tamyiz method in learning Arabic grammar to improve the skill of reading heritage books. Research Limitation- The study's limitations include its single-site focus at the Dinul Qoyyim Islamic Boarding School potentially limiting generalizability. The small sample size, focused on beginner students, may not fully represent broader educational contexts. Reliance on qualitative methods and a short duration restrict the depth of analysis and long-term impact assessment. Additionally, the specific cultural and religious context may affect applicability elsewhere. Future research should aim for broader sampling and longer-term assessments.